Management of leiomyosarcoma of the IVC, a rare vascular tumour, treated with adjuvant radiation therapy in a tertiary care hospital in India - Belani, Preeti; Basu, Sumit; Bhosale, Harshavardhan; Pilakkal, Shaju; Doiphode, Asmita; Mistry, Rajesh; Lad, Vidyadhar; Chattopadhyay, Somnath; Kulkarni, Bijal (International Journal of Research in Medical Sciences, 2025)
Leiomyosarcoma of the inferior vena cava (IVC) is an extremely rare malignancy, in an already rare subgroup of primary vascular malignancies, with nonspecific clinical presentation. The primary treatment modality is surgery and the disease outcome is dismal even after complete surgical resection. The role of adjuvant treatment (including Chemotherapy and Radiotherapy) is now being routinely considered. In this study, we have discussed a case of a 50 years old lady with good performance status, diagnosed with Leiomyosarcoma of the IVC. She was found to have a positive margin after extensive surgery and was treated with adjuvant External beam radiation therapy using VMAT technique in 2 phases. At 3 months after completing radiation treatment, her PET CT scan showed no evidence of disease and at 4 months follow up, she had good performance status with no major complaints. However, 5 months after completing treatment, she developed multiple liver metastases.